Féminisme radical et sexualité : « Le manifeste de l’asexualité » de Lisa Orlando (1972) - Élie Grau; Lisa Orlando (Glad!)
French translation of the Asexual Manifesto by Lisa Orlando. This document was written in the feminists/lesbian circles of the USA in the 1970s. It was published and shared during a few years before falling into oblivion until its rediscovery in 2019. The asexuality it describes is one of a political choice meant to fight against the sexism ingrained in every sexual relationships, no matter who they involve.